2013
DOI: 10.1039/c3cs60125k
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and advances in the field of self-assembled membranes

Abstract: Self-assembled membranes are of vital importance in biological systems e.g. cellular and organelle membranes, however, more focus is being put on synthetic self-assembled membranes not only as an alternative for lipid membranes but also as an alternative for lithographic methods. More investigations move towards self-assembly processes because of the low-cost preparations, structural self-regulation and the ease of creating composite materials and tunable properties. The fabrication of new smart membrane mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 52 publications
0
65
0
Order By: Relevance
“…At this concentration the particles assemble at the interface almost instantaneously to minimize air-water interaction energies (Scheme 1 ) and it was experimentally found that this concentration provides a monolayer arrangement and a complete surface coverage. [ 3,29,33 ] The particles at the interface are then irradiated with UV-light in order to induce inter-particle cross-linking. During irradiation, the sample is cooled on ice in order to keep the temperature below the lower critical solution temperature (LCST, 32-35 °C) of the polyNIPAAm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this concentration the particles assemble at the interface almost instantaneously to minimize air-water interaction energies (Scheme 1 ) and it was experimentally found that this concentration provides a monolayer arrangement and a complete surface coverage. [ 3,29,33 ] The particles at the interface are then irradiated with UV-light in order to induce inter-particle cross-linking. During irradiation, the sample is cooled on ice in order to keep the temperature below the lower critical solution temperature (LCST, 32-35 °C) of the polyNIPAAm.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] properties. [ 25,26 ] Ferritin (Horse spleen ferritin, HSF) is an iron storage protein in mammals and consists of a dodecameric protein cage of 12 nm in diameter with a 6 nm central cavity containing a phosphate ferrihydrite core.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, their performances cannot be improved significantly to tackle grand challenges in SusChEM including the development of (i) high flux and fouling-resistant membranes for water reclamation and resource recovery [3], (ii) low-energy desalination membranes with high water recovery [4] and (iii) high capacity and selective membrane absorbers for biochemical separations and purifications [5]. Mixed matrix membranes (MMMs) are the subject of increasing attention and interest due to their potential to serve as multifunctional membranes for SusChEM with improved properties and performance [6][7][8][9][10][11][12]. The convergence between membrane technology and nanotechnology is providing unprecedented opportunities to develop new MMMs with embedded nanoparticles that can carry out multiple functions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The convergence between membrane technology and nanotechnology is providing unprecedented opportunities to develop new MMMs with embedded nanoparticles that can carry out multiple functions (e.g. retention, sorption and catalysis) with higher permselectivity and flux, greater mechanical strength and lower fouling propensity [6][7][8][9][10][11][12]. Polymeric micro/nanoparticles (PMNPs) could provide greater flexibility for the preparation of MMMs with improved particle-matrix compatibility, particle loading, flux and permselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Charge-based effects can influence transport at length scales many times the size of the ion and form the basis of many ionic separation processes 18 . One of the key features for the development of model systems to capture the essential physics and chemistry of the process, which in turn can be used to generate a set of design principles to optimize a membrane's ionic separation performance, is the ability to independently control charge-based interactions for a given membrane morphology, either during the synthesis process itself or in additional steps of functionalization 19 .…”
mentioning
confidence: 99%